P168 Chemsex: A Health Needs Assessment for an Emerging Public Health Concern. (30th June 2016) - Tomkins, Andrew; Vivancos, Roberto; Kliner, Merav
Abstract : Background/introduction: Reports of sexualised drug taking (chemsex) have increased significantly in recent years. To establish the risks associated with chemsex and the services required by participants in Greater Manchester, a health needs assessment was undertaken. Aim(s)/objectives: To identify links between chemsex and adverse health outcomes, and to determine the perceived barriers seeking support. Methods: An online survey was devised, and then promoted with the support of local voluntary organisations and sexual health clinics. Data were analysed on acute Hepatitis C diagnoses for the previous 5 years using data collected by PHE. Interviews were conducted with key stakeholders. Results: In total, 54 participants completed the anonymous online survey, of which 52 were men who have sex with men (MSM). 76% were HIV positive and 20% were Hepatitis C positive. The most commonly used recreational drugs were Mephedrone (81%) and GHB/GBL (79%). Of respondents, 78% felt they would prefer to access support in a specialist clinic within a sexual health service. Qualitative data on barriers to accessing support were determined. Using PHE Acute Hepatitis C data, 46% of the 57 patients diagnosed via Greater Manchester sexual health clinics between 2009 – 2015 had used at least one chemsex drugs in the past 12 months. Stakeholder interviews gave insight into perceived barriers to accessing care. Discussion/conclusion: We identify demographic factors of chemsex users and the perceived barriers to accessing support. These findings will be useful in guiding commissioning and tailoring specialist services.